1996
DOI: 10.1159/000259190
|View full text |Cite
|
Sign up to set email alerts
|

On the Clinical Relevance of Mismatch Negativity: Results from Subjects with Normal Hearing and Cochlear Implant Users

Abstract: Mismatch negativity (MMN) provides an objective measure for evaluating subjects with problems related to speech processing. For a valid neurophysiological profile of speech-processing mechanisms, an efficient procedure to elicit MMNs is needed. In Experiment 1 of this study, MMN recordings were conducted in adults with normal hearing on the effects of decreasing the duration of the interstimulus interval (ISI). Shortening ISI duration does not seem to have a high impact on the individual MMN quality, whereas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 23 publications
(36 reference statements)
5
29
0
4
Order By: Relevance
“…After 2.5 years of CI use, a significant improvement in the open-set speech-discrimination test and an increase in the MMN amplitude for the small vowel difference (/e/-/ø/) were found. These results corroborate those of Kraus et al [1993] and Groenen et al [1996]. Although the present results with a small number of subjects can be considered preliminary, they provide evidence consistent with cortical plasticity associated with auditory memory and discrimination processes reflected by the MMN when relearning speech-sound processing after cochlear implantation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…After 2.5 years of CI use, a significant improvement in the open-set speech-discrimination test and an increase in the MMN amplitude for the small vowel difference (/e/-/ø/) were found. These results corroborate those of Kraus et al [1993] and Groenen et al [1996]. Although the present results with a small number of subjects can be considered preliminary, they provide evidence consistent with cortical plasticity associated with auditory memory and discrimination processes reflected by the MMN when relearning speech-sound processing after cochlear implantation.…”
Section: Discussionsupporting
confidence: 89%
“…Tervaniemi et al [1999] found a high test-retest reliability for the MMN, suggesting its usefulness even at the individual level. Groenen et al [1996] divided CI users into good and moderate ones, based on their behaviourally measured perceptual skills. The MMN for the contrast pair /ba/ vs. /da/ in the good CI users was similar to that of normally hearing controls, whereas the moderate CI users showed no MMN.…”
Section: Event-related Potentials (Erps)mentioning
confidence: 99%
See 1 more Smart Citation
“…MMN responses were derived by the traditional approach where the averaged ERP waveforms of the standards were subtracted from that recorded for the deviants in each of the two oddball runs (i.e., runs "a" and "b" in Figure 1). We employed this approach to extract the MMN because of its popularity with assessing both normal and clinical populations (e.g., Groenen et al 1996;Sasaki et al 2000;Sabri & Campbell, 2001;Näätänen et al 2004). Furthermore, earlier research from our group (Walker et al 2001) lead us to believe that, under comparable test conditions (i.e., same stimulus deviance, ISI, and recording parameters), the MMNs elicited from other extraction techniques are not significantly different.…”
Section: Methodsmentioning
confidence: 99%
“…Sin embargo otros estudios han encontrado que sólo en algunos de los pacientes con implantes cocleares se puede obtener un MMN. Esto se debería a las variaciones individuales de los pacientes implantados, lo que se correlaciona con el desempeño que tienen en tareas de discriminación de fonemas 55,56 . Esta dificultad en la obtención del MMN en algunos individuos ha limitado su utilidad clínica en pacientes con implante coclear.…”
Section: Implante Coclearunclassified